Internalizing Mental Disorders and Accelerated Cellular Aging Among Perinatally HIV-Infected Youth in Uganda - Kalungi, Allan; Womersley, Jacqueline S.; Kinyanda, Eugene; Joloba, Moses L.; Ssembajjwe, Wilber; Nsubuga, Rebecca N.; Levin, Jonathan; Kaleebu, Pontiano; Kidd, Martin; Seedat, Soraya; Hemmings, Sian M. J. (Frontiers in Genetics, 2019)
Introduction Internalizing mental disorders (IMDs) in HIV+ children and adolescents are associated with impaired quality of life and non-adherence to anti-retroviral treatment. Telomere length is a biomarker of cellular aging and shorter telomere length has been associated with IMDs. However the nature of this association is yet to be elucidated. Objective We aimed at determining the longitudinal association between IMDs and relative telomere length (rTL) and how this could be influenced by chronic stress among Ugandan perinatally HIV infected youth (PHIY). Methods IMDs comprised of depressive disorders, anxiety disorders and post-traumatic stress disorder and they (IMDs) were assessed using the locally adapted Child and Adolescent Symptom Inventory – 5. In 368 PHIY with any of the IMDs and 368 age- and sex- matched PHIY controls without any psychiatric disorder, rTL was assessed using quantitative polymerase chain reaction. Hierarchical cluster analysis was used to generate the three chronic stress classes (mild, moderate and severe). T-tests were used to assess the difference between baseline and 12 month’s rTL and the mean differences of rTL between cases and controls both at baseline and at 12 months. Linear regression analysis was used to model the effect of chronic stress on the association between IMDs and rTL, controlling for age and sex. Results We observed longer rTL among cases of IMDs compared with their controls (p<0.001). We also observed a statistically significant reduction in rTL between baseline and 12 months among a combined sample of cases and controls (p<0.001). The same statistical difference was observed when cases and controls were individually analyzed (p<0.001 respectively). We found no significant difference in rTL between cases and controls at 12 months (p=0.117). We found no significant influence of chronic stress on the association between IMDs and rTL both at baseline and 12 months. Conclusion rTL are longer among cases of IMDs compared to age- and sex-matched controls. We observed significant attrition in rTL over 12 month’s duration, which seems to be driven by the presence of any IMDs. There is a need for future longitudinal studies to understand the mechanisms driving our findings.